Seven practices for sustaining human resources in small and medium-sized enterprises - Hashim, Mohd Khairuddin (UUM Press, 2011)
Small and medium-sized enterprises (SMEs)need to develop and sustain their human resources in order to improve their competitiveness.Although human resources are essential to SMEs, the small business literature indicates studies that examined how these firms manage their human resource have not received much attention, particularly in Malaysia.This has resulted in limited knowledge on human resources practices among the local SMEs.The purpose of this paper is to address this issue.Based on the review of the literature and the evidence obtained from the findings of past studies, This paper identifies and seeks to provide owners and managers of SMEs some insights into seven human resource practices that can assist them to not only sustain their human resources but also help them to become more competitive.